The Impact of the United States-China Trade War on Indonesia's Sharia Economic Politics - Siti Muflihah; Wildia Nusayfi; Junaidi; Mashudi (Penerbit Hellow Pustaka, 2025)
Indonesia's economy is highly dependent on cooperation with other countries, especially in the field of imports and exports, and has a certain influence on its economic growth. The aim of this qualitative research is to explain how the US-China trade war has an impact on Indonesia's political economy. Qualitative research collects descriptive data from people's written and spoken behavior and words. This research collects data by reading documents or literature about trade wars and information from the internet. The US-China trade war is actually a big market opportunity to bridge the market gap between the two countries, so the impact of this trade war on Indonesia itself is not too big. This is because the products targeted in the trade war are not products that Indonesia exports to these two countries.